Marketing strategy of apparel and textile cluster in southwest region of Bulgaria - Mladenova, Galina (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
This paper provides an analysis of marketing activities and marketing organization of the Southwest apparel and textile cluster in Bulgaria. The first section of the paper gives an overview of the organization and functioning of the cluster. The second section focuses on the cluster marketing, analyzing its success to date and identifying the challenges it faces going forward. The purpose of the research report is to present and to analyze the marketing strategy of “Inter Moda Trading Cluster” in the Southwest region of Bulgaria. The sources of data which have been used in the research process are: official trade publications, cluster’s publications (internet site, bulletins, brochures, newsletters etc.), internal documents, depth interviews that were carried out with cluster’s top managers and the Chair of the Commercial Chamber in the city of Kyustendil.